Selective removal of dyes by molecular imprinted TiO2 nanoparticles in polysulfone ultrafiltration membrane. Issue 4 (August 2017) - Melvin Ng, H.K.; Leo, C.P.; Abdullah, A.Z.
Graphical abstract: Highlights: Molecular imprinting polymer was used to create selective TiO2 . The selective TiO2 degraded methylene blue and methylene orange selectively. The selective TiO2 was blended into the polysulfone ultrafiltration membrane. The selectivity of dye removal was further enhanced to 2.83. The membrane permeate flux was enhanced by blending the modified TiO2 . Abstract: The selective removal of target dye and the reuse of other dye in a dye mixture was achieved by modifying TiO2 with molecularly imprinted polymer (MIP-TiO2 ). MIP-TiO2 was further immobilized in polysulfone (PSf) ultrafiltration membrane to eliminate the recovery of the particles. MIP-TiO2, enhance the separation capability of PSf membrane and create the selectively photocatalytic property on PSf membrane. MIP-TiO2 achieved an ideal selectivity of methylene blue/methylene orange up to 2.00 within 5 cycles under the irradiation of UV. The selective MIP-TiO2 was blended into PSf membrane before phase inversion. The selectivity of dye removal was further enhanced to 2.83 using the PSf membrane blended with MIP-TiO2 nanoparticles in the integrated photodegradation-ultrafiltration process. The improvement was caused by the surface charge of PSf membrane. On the other hand, the permeability of PSf membrane was enhanced after incorporating MIP-TiO2 .